Statistical analysis of the performance of young's modulus of natural fiber composites and synthetic fiber composites - Muhammad, Noryani; Mohammad Taha, Mastura; Mustafa, Nuzaimah; Zakaria, Nazri Huzaimi; Che Hamid, Hazliza Aida; Shaharuzaman, Mohd Adrinata; Loh Y.F (Penerbit UTM Press, 2022)
Fiber-reinforced composites are widely used in a wide range of applications due to their lightweight, low cost, environmentally friendly, and reliable properties. Natural fiber and synthetic fiber are the two main types of fiber. These two fiber groups have distinct features that require a methodical approach for material selection. The distinct properties of both fibers resulted in a wide range of strength that was computed in accordance with the desired performance of material engineers. Synthetic fibers are known to be stronger than natural fibers, however due to sustainability concerns, natural fibers are commonly used with some fiber modifications and hybridization to enhance the strength of natural fiber composites. Statistical analysis is employed in this study to determine Young's modulus of each fiber group. Hypothesis testing was used to confirm the performance of the fiber's Young's modulus. All synthetic fibers have a substantially greater Young's modulus than natural fiber based on the P-value score. Aramid had the highest score for synthetic fibers, while flax fiber had the highest score for natural fiber groups, with 424.8 GPa and 57.3 GPa, respectively. Ultimately, hybridization has the potential to overcome the limitations of both synthetic and natural fibers. This statistical approach may be used to validate the hypothesis about the properties of both fibers.